The effect of the COVID-19 pandemic on Malaysian residential customers? energy-saving appliance purchasing behaviour - Jaaffar A.H.; Kasavan S.; Mustapa S.I.; Al-Amin A.Q. (Emerald Publishing, 2025)
Purpose: The COVID-19 pandemic has caused a dramatic impact on energy supply and demand. It is vital to understand households? behaviour with regard to energy, particularly during the pandemic, to deploy future sustainable energy systems. This study aims to investigate the nexus of Malaysian households? energy consumption behaviour in relation to various electrical appliances, their energy-saving appliance purchasing behaviour and their current possession of energy-saving appliances during the pandemic, especially during the lockdown period, from the perspective of the energy cultures framework. Design/methodology/approach: The partial least squares structural equation modelling technique was used to test hypothesised relationships based on the 1,485 pieces of household data collected using an online and physical survey during the lockdown period in Malaysia. Findings: The energy-saving behaviour cultivated due to the impact of the COVID-19 pandemic led to residential customers? intentions to purchase energy-saving appliances which subsequently led to their current possession of energy-saving appliances. Indeed, energy-saving behaviours in the kitchen, entertainment, office, home lighting and cooling appliances have more than 77.4% influence on their purchasing behaviour. The consumer?s purchase behaviour for energy-saving appliances has a significant, partially mediating influence on the energy-saving behaviour of various electrical appliances and the consumers? current possession of energy-saving appliances. Research limitations/implications: This study could be enhanced by improving the sample using a higher-income group and involving other parts of Malaysia such as the southern region. The findings do extend the energy cultures framework by demonstrating the mediating role of households? energy-saving appliance purchasing behaviour on the relationship between their energy consumption behaviour in relation to various electrical appliances and their current possession of energy-saving appliances. Practical implications: The results of this study will help develop future action plans for transitioning to energy-saving appliance practices. Originality/value: This paper examines the effects of the COVID-19 pandemic on future energy efficiency practices in developing countries from the perspective of the energy cultures framework. ? 2023, Emerald Publishing Limited.